Formal techniques for networked and distributed systems--FORTE 2002 : 22nd IFIP WG 6.1 international conference, Houston, Texas, USA, November 11-14, 2002 : proceedings /: 22nd IFIP WG 6.1 international conference, Houston, Texas, USA, November 11-14, 2002 : proceedings. (2018) - Unknown
No abstract available